Probing the electrical switching of a memristive optical antenna by STEM EELS - David T. Schoen (Nature Portfolio, 2016)
Scaling of photonic devices requires materials with sufficiently strong elecro-optic effects. Here, Schoen et al.demonstrate and analyze single electrically induced switching events that can operate in the visible with a small active volume using electron energy loss in a scanning transmission electron microscope.